Understanding mass media - Schrank, Jeffrey (Lincolnwood, Ill. National Textbook, 1991)
A textbook examining the importance of the mass media as means of communication and as shapers of the environment.
Includes index.
Keywords: Mass media; Communication; Telecommunication